Uterine Cervix-Benign Histomorphological Spectrum - Basnet, Sunila; KC, Shiva Raj; KC, Geetika (Nepalese Medical Journal, 2018)
Introduction: Non neoplastic lesions of cervix form a wide variety of lesions in the cervical biopsy specimen or hysterectomy specimens. Chronic cervicitis is the commonest finding; but can be associated with other underlying pathologies. In our study we aim to study and categorize the morphology of non neoplastic lesions of cervix in cervical biopsy specimen or hysterectomy specimens into inflammatory, reparative or reactive lesions, glandular hyperplasia, metaplasia and ectopies and benign neoplasm. Materials and Methods: This is a retrospective study that consisted of 520 slides retrieved from the records of department of histopathology KIST medical college. Whenever required block were retrieved and recut sections were made. All the benign lesions were included in the study. Results: The commonest lesions diagnosed were inflammatory, reparative or reactive changes 513 (98.6%) cases, followed by metaplastic changes 311 (59.8%) and glandular hyperplasia in 44 cases (8.4%). Benign neoplasms were seen in 33(6.3%) cases. Conclusions: Cervix is a target organ for varieties of neoplastic and non neoplastic diseases. There are many benign mimics of malignant cervical lesions. It may be difficult to interpret adequately in a small biopsy specimen however it is necessary to distinguish between these benign lesions and their mimics to prevent unnecessary inappropriate treatment to the patient. Nepalese Medical Journal. vol.1, No. 1, 2018, Page : 1-4